Affinity Lens: Data-Assisted Affinity Diagramming with Augmented Reality - Subramonyam, Hariharan; Drucker, Steven; Adar, Eytan (SIGCHI, 2019)
Despite the availability of software to support Affinity Diagramming (AD), practitioners still largely favor physical sticky-notes. Physical notes are easy to set-up, can be moved around in space and offer flexibility when clustering unstructured data. However, when working with mixed data sources such as surveys, designers often trade off the physicality of notes for analytical power. We propose Affinity Lens, a mobile-based augmented reality (AR) application for Data-Assisted Affinity Diagramming (DAAD). Our application provides just-in-time quantitative insights overlaid on physical notes. Affinity Lens uses several different types of AR overlays (called lenses) to help users find specific notes, cluster information, and summarize insights from clusters. Through a formative study of AD users, we developed design principles for data-assisted AD and an initial collection of lenses. Based on our prototype, we find that Affinity Lens supports easy switching between qualitative and quantitative ‘views’ of data, without surrendering the lightweight benefits of existing AD practice.
Best Paper Award